Using metaphors to gain insight into South African student teachers’ initial and developing conceptions of ‘Being a teacher’ - Rusznyak, L.; Walton, E. (My University, 2014)
Metaphors are a useful way of accessing students' conceptions of teaching and tracking how their conceptions shift over time. This article analyses metaphors for ‘being a teacher’ written by a group of South African student teachers at the beginning and end of their first year of study. The metaphors depict teachers' interactions with learners and reveal how students recognise a specialised knowledge base for teaching and their understanding of learner diversity. One third of students constructed initial metaphors that emphasised teaching as nurturing, an endeavour they associate with particular personality traits but without a specialised knowledge base. We analyse how student teachers' initial and subsequent metaphors reflect significant shifts in their conception of ‘being a teacher’ and we briefly explore how students account for these shifts. Revisiting their initial assumptions about teaching within a programme that offers a coherent conception of teaching enabled student teachers to better understand the goals of initial teacher education.